PATCHOULI ALKOHOL ISOMERS POGOSTEMON HERBA PREDICTED VIRTUALLY - Sentot Joko Raharjo; Chanif Mahdi; Nurdiana Nurdiana; Wolfgang Nellen; Fatchiyah Fatchiyah (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
The aim of our research is predicting the alpha-patchouli alcohol isomer Pogostemon Herba as inhibitors cyclooxygenase (COX-1 and COX-2) isoenzymes. The data for the alpha-patchouli alcohol isomer (CD521903, CD442384, and/or CD6432585) Pogostemon Herba were explored from the pubchem database. Molecular interaction studies with COX-1 and COX-2 from mouse were done using the molecular docking tools Hex 6.12 and LeadIT2 Bisolve. The analysis of the alpha-patchouli alcohol compounds of patchouli oil showed that alpha-Patchouli alcohol (CD521903) binds to COX-1 at active sites including: LEU223B, ASP228B, LEU237B, ARG 332B, TRP 138A, GLU 139A, SER 142A, ASN 143A, and the interaction to COX-2 at active site including: GLN 289B, GLU 290B, ARG 222B, LYS 211B, THR 212B, HIS 214B, ASN 382B, HEM682B, GLN 454B, HIS 386B, TRP 387B, HIS 388B, VAL 274B, GLN 203B, VAL 291B, VAL 295B. The interaction hydrogen bond energy between alpha-patchouli alcohol: (CD521903-COX-1 complexes (-4 kJ/mol) and CD521903-COX-2 complexes (-8 kJ/ mol) by LeadIT2 Biosolve. This suggests alpha-patchouli alcohol CD521903 as candidate for a selective COX-2 inhibitor. These in silico data need further analyses of biological function activity.